A new dung beetle species of the genus Stiptopodius Harold, 1871 (Coleoptera: Scarabaeidae: Scarabaeinae) recorded from xeric savanna in Namibia - Strümpher, Werner P.; Daniel, Gimo M. (Zootaxa, 2021)
A new species of dung beetle, Stiptopodius brancoi Strümpher & Daniel, new species, from Namibia, is diagnosed, described, and illustrated. The new species is the first Stiptopodius recorded from the country and belong to the “singularis species group”. A revised key as well as a checklist of Stiptopodius species recorded from the African continent are provided.